2020
DOI: 10.3389/fnins.2020.00644
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Wwox Perturbs Neuronal Migration and Impairs Early Cortical Development

Abstract: We acknowledge the support from Enea-Eroi in ricerca onlus (www.eneaonlus.org). We also gratefully acknowledge the family for their participation to this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 46 publications
6
28
0
Order By: Relevance
“…In agreement with our findings, a recent study that examined the brain histology of a fetus suffering from the WOREE syndrome reported anomalous migration of the external granular layer within the molecular layer of the cortex, a phenotype that was validated also in a rat model with spontaneous WWOX mutations (Iacomino et al , 2020 ). This observation is further supported by the transcriptomic analysis performed by Kosla et al ( 2019 ) on human neuronal progenitor cells (hNPCs) after silencing WWOX using shRNA.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our findings, a recent study that examined the brain histology of a fetus suffering from the WOREE syndrome reported anomalous migration of the external granular layer within the molecular layer of the cortex, a phenotype that was validated also in a rat model with spontaneous WWOX mutations (Iacomino et al , 2020 ). This observation is further supported by the transcriptomic analysis performed by Kosla et al ( 2019 ) on human neuronal progenitor cells (hNPCs) after silencing WWOX using shRNA.…”
Section: Discussionsupporting
confidence: 92%
“…The authors also reported decreased mitochondrial redox potential, enhanced cellular adhesion to the growth surface, and reduced expression of MMP2 and MMP9. Iacomino et al ( 2020 ) reanalyzed this transcriptomic data, focusing on genes associated with neuronal migration and differentiation, and found reduced expression of some neural migration‐related genes, such as microtubule proteins and kinesin family proteins. Notably, cortical layering was found to be affected by the status of the Wnt pathway (Qian et al , 2020 ), a pathway in which WWOX has been implicated through its binding partners.…”
Section: Discussionmentioning
confidence: 99%
“…Hypomyelination with atrophy of the optic tract and cerebellar foliar white matter were also observed [ 38 ]. Interestingly, some of these observations agree with a recent report describing neuronal disorganization with defective architecture of the granular and molecular cell layers of cerebral cortex in brain histology samples from a WWOX null human fetus [ 39 ].…”
Section: Wwox-associated Cns Disorderssupporting
confidence: 91%
“…Transcriptional analysis of neurospheres derived from WWOX KO neural stem cells reveals alterations in the expression of genes related to neurological disorders, CNS development, and epilepsy [ 41 ]. Furthermore, transcriptomic analysis in WWOX-depleted human neural progenitor cells demonstrates that WWOX downregulation significantly alters the expression of genes involved in neuron migration and cytoskeleton organization [ 20 , 42 ]. Despite these studies, it is evident that detailed studies uncovering the molecular and cellular roles of WWOX in pediatric epilepsy are still lacking.…”
Section: Modeling Wwox Deficiency In Rodents Reveals An Epileptic Phenotypementioning
confidence: 99%